VALUE RELEVANCEOF EARNINGS PER SHARE AND BOOK VALUE OFEQUITY AMONG AUTOMOTIVE SUBSECTOR COMPANIES IN INDONESIA STOCK EXCHANGE (IDX) - A S P, Dewi Octavia (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to analyze the influence of value relevance of earnings per share and book value of equity to the stock price of Sub Sector Automotive & Components companies listed on the Indonesia Stock Exchange. The population in this study is Sub Sector Automotive & Components go public companies in Indonesia Stock Exchange as many as 12 companies. The sampling was done through purposive sampling method based on several considerations or criteria. The criteria are the companies must be Sub Sector Automotive & Components companies that have gone public and listed in IDX from 2011 until 2013. The data in this study was analyzed using multiple regression The results showed that earnings per share is relevant to measure firm value. The book value of equity is relevant to measure firm value.Based on these results, investor needs to consider the value of earnings per share and book value of equity in making any investment decision because it is important to assess the potential revenue to be accepted. Keywords: Value Relevance of Accounting Information, Earnings Per Share, and Â  Book Value of Equity